2006
DOI: 10.1063/1.2217375
|View full text |Cite
|
Sign up to set email alerts
|

Two-color visible/vacuum ultraviolet photoelectron imaging dynamics of Br2

Abstract: An experimental two-color photoionization dynamics study of laser-excited Br2 molecules is presented, combining pulsed visible laser excitation and tunable vacuum ultraviolet (VUV) synchrotron radiation with photoelectron imaging. The X 1Sigmag + -B 3Pi0+u transition in Br2 is excited at 527 nm corresponding predominantly to excitation of the v' = 28 vibrational level in the B 3Pi0+u state. Tunable VUV undulator radiation in the energy range of 8.40-10.15 eV is subsequently used to ionize the excited molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A caveat of course is that high repetition rate and/or cw laser systems will be necessary to take advantage of the continuous nature of the source. Attempts toward this have been demonstrated recently utilizing both IR 42 and visible 43 lasers coupled to a synchrotron.…”
Section: Resultsmentioning
confidence: 99%
“…A caveat of course is that high repetition rate and/or cw laser systems will be necessary to take advantage of the continuous nature of the source. Attempts toward this have been demonstrated recently utilizing both IR 42 and visible 43 lasers coupled to a synchrotron.…”
Section: Resultsmentioning
confidence: 99%
“…1 kHz) have been merged with the synchrotron to produce some two color or pumpprobe types of measurements. [83][84][85] At major facilities of the future, typically involving the principle of free electron laser (FEL) outputs, 86 the electron emittence is low enough and the undulator emission is high enough to produce laser-like gain over a long undulator path length. Time dynamics and coherence properties will become major new ways to access dynamics in the vacuum ultraviolet, soft X-ray, and hard X-ray regimes.…”
Section: Imaging Mass Spectrometrymentioning
confidence: 99%
“…The signals of the transient state are taken from Ϫ33 fs to ϩ165 fs in steps of 33 fs, and it is found that the highest peak of the transient state is slightly delayed in time, which is consistent with the presumption that Br 2 molecule is ionized after it has moved out on the dissociative curve with a small time delay. Meanwhile, we find that the signal counts of the transient state will shift to lower energies with longer time delays, which can only be elucidated by employing much shorter time resolution probe pulses in experiment [17,18].…”
Section: Resultsmentioning
confidence: 96%
“…Meanwhile, by utilizing the novel pump‐probe experiment Nugent–Glandorf find that the electron distribution will change on an ultrafast time scale to accommodate the moving nuclei after the chemical bond is broken. Recently, laser‐excited Br 2 molecule has been studied by the method of two‐color photoionization dynamics 17, and also a series of ultrafast photoelectron spectra of the gas phase dissociation of Br 2 molecule have been obtained, which contain information about the electronic structure of the reactants and products 18, 19. Here, we apply the time‐dependent‐wave‐packet method to study the chemical bond of Br 2 molecule evolving after excitation to C 1 ∏ u state, the appearance of atomic‐like peaks, and the ionization from excited states.…”
Section: Introductionmentioning
confidence: 99%